The Influence of Health Counseling on Knowledge and Attitude Regarding Healthy Diet in Type II Diabetes Melllitus Patients in Tomuan Health Center, Pematang Siantar City in 2021 - Suzan Fhitriana; Natallina Sidabutar; Dian Mayasari (Pena Cendekia Insani, 2022)
Background: Type 2 Diabetes Mellitus (DMT2) constitutes 90% of all DM cases in the world, in Indonesia it has reached more than 16 million people and at the Tomuan Health Center, Pematangsiantar City in April 2021 there were 54 people. Objectives: This study aims to determine the effect of health education on knowledge and attitudes about a healthy diet in people with diabetes mellitus type II at the Tomuan Health Center, Pematang Siantar City in 2021. Method: This research is a Quasy Experimental type of research with the One Group Pretest Posttest design. The research was conducted at the Tomuan Health Center from October 2021 to March 2022. The sample for this study were 55 people with Type II Diabetes Mellitus. The analysis used the t-paired sample test, which compared data before and after being given counseling, and obtained the mean difference between pre-test and post-test. 95% significance level (? = 0.05). Result: showed that there were 47 people who experienced an increase in knowledge after treatment, the mean rank was 25.91 and there was an increase in the average attitude before treatment from 19.73 to 30.20 after treatment. The statistical test results for the knowledge variable obtained a p value of 0.000 <0.05 and for the attitude variable a p value of 0.007 <0.05. Conclusion: The conclusion of this study is that there is an effect of health education on knowledge and attitudes about a healthy diet in people with Diabetes Mellitus Type II at the Tomuan Health Center.